We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
229
1
avatar+166 

A parabola with equation y=ax^2+bx+c has a vertical line of symmetry at x=2 and goes through the two points (1,1) and (4,-1). The quadratic ax^2 + bx +c has two real roots. The greater root is sqrt(n)+2. What is n?

 Jul 26, 2018

Best Answer 

 #1
avatar+100173 
+2

A parabola with equation y=ax^2+bx+c has a vertical line of symmetry at x=2 and goes through the two points (1,1) and (4,-1). The quadratic ax^2 + bx +c has two real roots. The greater root is sqrt(n)+2. What is n?

 

has a vertical line of symmetry at x=2    so     

\(\frac{-b}{2a}=2\\ b=-4a\)

 

\(y=ax^2+bx+c\\ y=ax^2-4ax+c\)

 

goes through the two points (1,1) and (4,-1).

 

\(y=ax^2-4ax+c\\ 1=a-4a+c\\ 1=-3a+c\\ c=1+3a\\~\\ y=ax^2-4ax+1+3a\\ -1=16a-16a+1+3a\\ -2=3a\\ a=-2/3\\~\\ y=\frac{-2x^2}{3}+\frac{8x}{3}-1\\ \)

 

\(x = {-b \pm \sqrt{b^2-4ac} \over 2a}\\ x = \frac{\frac{-8}{3} \pm \sqrt{\frac{64}{9}-\frac{8}{3}} }{\frac{-4}{3}}\\ x = \frac{\frac{8}{3} \pm \sqrt{\frac{64}{9}-\frac{8}{3}} }{\frac{4}{3}}\\ x = \frac{\frac{8}{3} \pm \sqrt{\frac{64}{9}-\frac{24}{9}} }{\frac{4}{3}}\\ x = \frac{\frac{8}{3} \pm \sqrt{\frac{40}{9}} }{\frac{4}{3}}\\ x = \frac{8 \pm \sqrt{40} }{4}\\ x=2\pm\frac{\sqrt{10}}{2}\\ \text{The great root is}\\ x=2+\frac{\sqrt{10}}{\sqrt4}\\ x=2+\frac{\sqrt{10}}{\sqrt4}\\ x=\sqrt{2.5}+2\)

 

n=2.5

 Jul 26, 2018
 #1
avatar+100173 
+2
Best Answer

A parabola with equation y=ax^2+bx+c has a vertical line of symmetry at x=2 and goes through the two points (1,1) and (4,-1). The quadratic ax^2 + bx +c has two real roots. The greater root is sqrt(n)+2. What is n?

 

has a vertical line of symmetry at x=2    so     

\(\frac{-b}{2a}=2\\ b=-4a\)

 

\(y=ax^2+bx+c\\ y=ax^2-4ax+c\)

 

goes through the two points (1,1) and (4,-1).

 

\(y=ax^2-4ax+c\\ 1=a-4a+c\\ 1=-3a+c\\ c=1+3a\\~\\ y=ax^2-4ax+1+3a\\ -1=16a-16a+1+3a\\ -2=3a\\ a=-2/3\\~\\ y=\frac{-2x^2}{3}+\frac{8x}{3}-1\\ \)

 

\(x = {-b \pm \sqrt{b^2-4ac} \over 2a}\\ x = \frac{\frac{-8}{3} \pm \sqrt{\frac{64}{9}-\frac{8}{3}} }{\frac{-4}{3}}\\ x = \frac{\frac{8}{3} \pm \sqrt{\frac{64}{9}-\frac{8}{3}} }{\frac{4}{3}}\\ x = \frac{\frac{8}{3} \pm \sqrt{\frac{64}{9}-\frac{24}{9}} }{\frac{4}{3}}\\ x = \frac{\frac{8}{3} \pm \sqrt{\frac{40}{9}} }{\frac{4}{3}}\\ x = \frac{8 \pm \sqrt{40} }{4}\\ x=2\pm\frac{\sqrt{10}}{2}\\ \text{The great root is}\\ x=2+\frac{\sqrt{10}}{\sqrt4}\\ x=2+\frac{\sqrt{10}}{\sqrt4}\\ x=\sqrt{2.5}+2\)

 

n=2.5

Melody Jul 26, 2018

12 Online Users

avatar
avatar
avatar